Imidazonaphthyridine effects on Chikungunya virus replication: Antiviral activity by dependent and independent of interferon type 1 pathways - Ruiz, Uriel Enrique Aquino; Santos, Igor Andrade; Grosche, Victória Riquena [UNESP]; Fernandes, Rafaela Sachetto; de Godoy, Andre Schutzer; Torres, Jhoan David Aguillón; Freire, Marjorie Caroline Liberato Cavalcanti; Mesquita, Nathalya Cristina de Moraes Roso; Guevara-Vega, Marco; Nicolau-Junior, Nilson; Sabino-Silva, Robinson; Mineo, Tiago Wilson Patriarca; et al. (Elsevier, 2023)
The Chikungunya virus (CHIKV) causes Chikungunya fever, a disease characterized by symptoms such as arthralgia/polyarthralgia. Currently, there are no antivirals approved against CHIKV, emphasizing the need to develop novel therapies. The imidazonaphthyridine compound (RO8191), an interferon-α (IFN-α) agonist, was reported as a potent inhibitor of HCV. Here RO8191 was investigated for its potential to inhibit CHIKV replication in vitro. RO8191 inhibited CHIKV infection in BHK-21 and Vero-E6 cells with a selectivity index (SI) of 12.3 and 37.3, respectively. Additionally, RO8191 was capable to protect cells against CHIKV infection, inhibit entry by virucidal activity, and strongly impair post-entry steps of viral replication. An effect of RO8191 on CHIKV replication was demonstrated in BHK-21 through type-1 IFN production mechanism and in Vero-E6 cells which has a defective type-1 IFN production, also suggesting a type-1 IFN independent mode of action. Molecular docking calculations demonstrated interactions of RO8191 with the CHIKV E proteins, corroborated by the ATR-FTIR assay, and with non-structural proteins, supported by the CHIKV-subgenomic replicon cells assay.
Keywords: Antiviral activity; Chikungunya Fever; Chikungunya virus; Imidazonaphthyridine; Neglected tropical diseases; Type-1 IFN independent activity